SAT0208 Inflammatory Myopathies Associated with Sjögren's Syndrome Do Not Differ from Those without Sjögren's Syndrome Aside from Older Age at Diagnosis and Less Frequent Normal Muscle Biopsy. (15th July 2016) - Meyer, A.; Maurier, F.; Larroche, C.; Tournadre, A.; Dieudé, P.; Dernis, E.; Vittecoq, O.; Dubost, J.-J.; Fauchais, A.-L.; Mariette, X.; Sibilia, J.; Gottenberg, J.-E.
Abstract : Background: Prevalence of Sjogren's syndrome (SS) in inflammatory myopathies (IM) and whether IM patients with SS represent a distinct disease subset are currently unknown. Objectives: To assess the signification of SS in IM with regard to phenotype and prognosis. Methods: IM patients with SS (IM-SS group) were identified among a cohort of 270 patients with IM using European-American Consensus Group (EACG) classification criteria. Clinical, serological, muscle pathological features, management and outcomes of IM-SS patients were retrospectively studied and compared to the IM patients who had been assessed for SS but did not fulfill these criteria (IM-noSS group). Results: EACG criteria were available in 63 IM patients of the total cohort and 29 (46%) were diagnosed as having SS. These IM-SS patients were older at IM diagnosis than the 34 IM-noSS patients (56±3.1 vs 47.7±2.8 years, p=0.05), sex ratio wasn't different. SS was mostly diagnosed at the time of IM diagnosis (n=23, 79%) and less frequently preceded (n=3: 1, 3 and 4 years) or followed (n=3, 3, 6 and 30 years) IM diagnosis. IM-SS patients had subjective sicca syndrome (29/29, 100%) with objective dryness (10/12, 92%), anti-SSA/SSB antibodies (14/29, 48%) and/or focus score ≥3 in minor salivary glands biopsy (n=21/24, 88%). Creatine kinase level was not different between IM-SS and IM-noSS (1400±320 vs 2538±214 UI/L, p=0.5). A normal muscle biopsy was less frequently found in IM-SS than in IM-noSS patient (7/28 vs 1/24 p=0.05). According to the ENMC criteria, DM was the more frequent muscle histological finding in IM-SS patients (n=10, 42%) but all histological patterns were represented (including nonspecific IM: 6 (25%), inclusion body myositis: 4 (17%), polymyositis: 2 (8%), necrotizing myopathy: 1 (4%). This distribution was not different from the IM-noSS group. IM-SS patients also suffered from interstitial lung disease (n=10, 34%), arthralgia and/or arthrithis (n=17, 59%), skin involvement (n=14 48%) and Raynaud syndrome (n=14, 48%) which occurrence characteristics were not different from IM-noSS group. Anti-SSA (n=13, 45% vs n=1, 3%, p=0.0001) and anti-SSB (n=6, 21% vs n=0, 0% p<0.01) were more frequent in IM-SS groups. Other auto-antibodies were found in 14 IM-SS patients (48%) and in 19 IM-noSS patients (56%, p=0.62) which specificities were not significantly different between the two groups. Cryoglobulin was also found with a similar frequency in both groups (n=3, 10% vs n=3, 9%; p=1.0). Six IM-SS patients (21%) were diagnosed with cancer versus 4 IM-noSS patients (12%) (p=0.49). Mean number of treatment was not different between the two groups (1.9±0.2951 vs 1.6±0.2616; p=0.41) and after a follow-up >7 years, 6 patients died in both groups, whithout any significant difference in survival (p=0.23). Conclusions: SS is frequently observed in IM. No difference was found between IM-SS and IM-noSS with regards to phenotype, serotype and survival aside from older age at diagnosis and less frequent normal muscle biopsy. Disclosure of Interest: None declared